METHOD OF BUILDING PROPRIETARY TEMPLATES FOR INFORMATION ENCRYPTION AND COMPRESSION TASKS - ROZLOMII, INNA; NAUMENKO, SERHII (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article presents a novel approach to building author’s templates for encryption and compression tasks. The use of author’s templates provides a secure and efficient way of encrypting and compressing information, as they offer a unique prototype for cipher templates that can be used for a wide range of applications. The proposed method for constructing author’s templates is based on a statistical analysis of English language texts and the use of modular cryptographic transformation of numbers from a given range. The approach involves breaking down the text into smaller chunks and analyzing the frequency of occurrence of letters and combinations of letters within each chunk. The results of this analysis are then used to construct a matrix that determines the rules for distributing symbols in the author’s template. The constructed author’s template is a prototype of a cipher template and is similar to the Cardano’s grid. The author’s template provides a secure way of encrypting and compressing information, as the symbols are distributed in a random and unique way, making it difficult for unauthorized parties to decipher or decompress the information. The proposed method allows for the creation of author’s templates for a wide range of encryption and compression tasks. The input data for constructing author’s templates are an English language text and a matrix that determines the rules for distributing symbols in the author’s template. Changing the input data allows for the creation of new author’s templates that can be tailored to specific applications or requirements. In conclusion, the method presented in this article offers a unique and efficient way of constructing author’s templates for encryption and compression tasks. The use of author’s templates provides a secure and reliable way of encrypting and compressing information, making it an ideal solution for applications that require secure data transmission and storage.